Relational and Cultural Impacts on the Work Life of Young Indigenous Men - Spowart, J. K. Payden; Marshall, E. Anne (Canadian Journal of Counselling and Psychotherapy, 2015)
Little is known about the unique experiences of Indigenous people in their work life journeys. In particular, there has been very little research on this topic specifically with young males. In this qualitative study, eight young Indigenous men shared their stories regarding their search for and engagement in work and education. The research question was «What are the supports, challenges, and obstacles experienced as you search for and maintain work?» Thematic analysis identified metathemes and themes related to their work life experiences. The results have important implications for theory, research, and practice in regards to work and career development with young Indigenous men.